Success of Low Aromatic Fuel in Preventing Gasoline Sniffing Deaths. (16th December 2022) - Stephenson, Lilli; Grabowski, Marc; van den Heuvel, Corinna; Humphries, Melissa; Byard, Roger W.
Abstract: Gasoline (petrol) sniffing is a form of volatile substance misuse that is particularly prevalent within Australian indigenous communities. Although epidemiological studies have shown that gasoline sniffing has decreased over recent years, rates of gasoline sniffing deaths have not been widely reported. Therefore, a study was undertaken to assess the association between the implementation of low aromatic fuel (LAF) and gasoline sniffing deaths. All cases of fatal gasoline sniffing in South Australia between 2000 and 2019 were identified from the Toxicology Database and autopsy reports at Forensic Science South Australia. Furthermore, previous studies of gasoline sniffing deaths were assessed to provide historical context and approximate rates of gasoline sniffing deaths before the current study. The rate of gasoline sniffing deaths decreased significantly ( P = 0.039) over the study period concomitant to an increase in the number of LAF sites nationally. Although not supported by findings of statistical significance because of the small number of cases, this study provides further supportive evidence for the effectiveness of LAF by showing a significant associated decrease in local rates of gasoline sniffing deaths.